Analysis of match activities in elite soccer referees during actual match play - D'Ottavio, S.; Castagna, C. (The Journal of Strength and Conditioning Research, 2001)
This study describes the work-rate profile of Italian high-level soccer referees (N = 33). The referees were examined during official games (n = 96) of the 1992-1996 first division Italian championships (Series A). Subjects were all experienced, top-level referees enrolled in the Commissione Arbitri Nazionali and officiated in the Series A and B Italian championships. Mean age of the referees studied was 37.8 ± 2.1 years. Match analysis was performed using a technology similar to that reported by Ohashi et al. in 1988. Average match distance was 11,469 ± 983 m. Referees, on average, covered 17.2% of the entire match distance at speeds faster than 18.1 km;pdh1. A 4.1% decrement of the total distance covered was evident during the second half (p ;lt 0.001). Furthermore, less distances were covered running backward and sideways during the second half compared to the first half (p ;lt 0.001). Nevertheless, the referees experienced no decrement in the distance covered at speeds faster than 18.1 km;pdh1 throughout the match. Match analysis revealed the intermittent nature of the referees' activities. Their intensity varied from situation to situation, frequently reaching near maximal intensity. However, sprint bouts never lasted for more than a few seconds (2-4 seconds). Therefore, refereeing, at least at top level, places unique stresses on the officials, and thus specific training and fitness assessment are needed.